(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Foreign language study has been increasingly important, as well as study of Thai language and culture by Chinese people which is getting more and more popular every year. The purpose of this research was to study anxiety problems and solutions of Thai teachers that experienced in preparing to teach Thai language in Chinese Universities. This research is a case study limited to 6 of Thai teachers from Chiang Mai University, Chiang Mai, Thailand, purposefully selected to conduct the individual interview process which was followed by the qualitative method. The In-depth interviews were undertaken with a range of teachers in Year 2018 to 2019. The data was analyzed manually by using Content Analysis after the data collection over. Both experienced teachers and non-experienced teachers felt anxious as the same which different factors come into play. Mostly, there are lots of negative feelings but anxiety experiences could be the driving force that made these teachers prepares more before going on to be Thai teachers in Chinese universities. It was not a bad experience only but was a very memorable once in a life time one for this teacher to share and guide future teachers